Fractures of the talus: where are we now?. Issue 1 (February 2023) - Kelleher, Joshua Francis; Patel, Riana; Bua, Nelson; Vemulapalli, Krishna
Abstract: The talus provides a crucial role in ankle stability and joint movement. If the talus is damaged, the collective motion of the foot and ankle becomes compromised, and significant disability or chronic pain can result secondary to complications including post-traumatic osteoarthritis, infection, and avascular necrosis. Talus fractures are challenging to treat due to their multiple articulations, precarious vascularity, and confined anatomical location. Long-term outcomes after talar fractures have historically been poor. Surgical management is advised for most displaced fractures of the talus in suitable patients. Goals of surgical treatment focus on meticulous anatomic reconstruction, preservation of blood supply, and stable fixation to encourage fracture union. This review summarizes the literature findings to provide a clearer view of the recommended management for each type of talus fracture. This article addresses individual talus fracture subtypes, including lateral process, posterior process, head, body, neck, and extrusion of the talus. In each section, we address assessment, management options, and known outcomes. The reader is also reminded of how to assess the commonly missed talus subtype fractures, particularly lateral process, posterior process and the talar head, where high index of suspicion is paramount even following a low-energy injury mechanism. Appropriate counselling is recommended to inform and educate patient about the long-term morbidity associated with talar fractures.